ANSWER:
(a)
(b)
Explanation:
(a)
We must do the following transformation:
![y=f(x)\rightarrow y=f(-x)](https://img.qammunity.org/2023/formulas/mathematics/college/te7v5uas52bf2kz55p1as9v02qq0pu29xf.png)
In this case, reflects f(x) about the y-axis. The rule that follows the above, is like this:
![(x,y)\rightarrow(-x,y)](https://img.qammunity.org/2023/formulas/mathematics/college/ikcitr9ov18gnuy0131ezdtc936qt485rg.png)
We apply the rule to the points of the function and it would be:
![\begin{gathered} \mleft(-4.2\mright)\rightarrow(4,2) \\ (0,4)\rightarrow(0,4) \\ (4,6)\rightarrow(-4,6) \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/ksd2ubwatf1re1g9mdrvp0gigsug2y51ru.png)
We graph and we have:
(b)
We must do the following transformation:
![y=g(x)\rightarrow y=-g(x)](https://img.qammunity.org/2023/formulas/mathematics/college/lp3th40fvbm2p3qrhg0md4sa89t8oqlewn.png)
In this case, reflects f(x) about the x-axis. The rule that follows the above, is like this:
![(x,y)\rightarrow(x,-y)](https://img.qammunity.org/2023/formulas/mathematics/college/d7a29ae1nc5itoub5zbvfqbwxpczq9rzr6.png)
We apply the rule to the points of the function and it would be:
![\begin{gathered} \mleft(-7,-2\mright)\rightarrow\mleft(-7,2\mright) \\ \mleft(-4,-5\mright?)\rightarrow\mleft(-4,5\mright) \\ \mleft(4,-1\mright)\rightarrow\mleft(4,1\mright) \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/b6uns7o98b28oc136ncmnigjlqbapnzpgd.png)
We graph and we have: